Gestão estratégica de resíduos sólidos: utilização do balanced scorecard - Souza, Ricardo Gabbay de (2007)
The public sector services are sited in a very dynamic environment, forcing their administrators to have a good perceiving of the internal and external factors that determine the systems reality. Particularly for the solid waste management in Brazil, this universe is defined by political pressures and limitations, influences by population s consuming patterns and environmental inadequacies. For a sustainable development in these systems, it is necessary aligning the many aspects to the sustainability principles, conceiving a strategy for action. Actually a very used tool for strategy management is Balanced Scorecard, which main advantages are: the analysis of organizations positioning under many perspectives, above the strictly financial and operational focus; and the construction of a strategy map, that visually communicates the hierarchy of organizations intended goals. It is also structured a card composed of objectives and their related measures, goals and initiatives, both at organizational and departmental levels. This research analyses the applicability of this method for the solid waste management, using as case a simulated Trust between Araraquara e São Carlos-SP. This permitted working with more than one vision for the strategy, including system s most probable management function workers. The results point to a great applicability of the tool, and instead of the few adequations it was kept the standard structure of the original model, clearly showing a strategic hierarchy from learning and growth and internal processes to society and institutional aspects.